2014
DOI: 10.3389/fnhum.2014.00885
|View full text |Cite
|
Sign up to set email alerts
|

The complete design in the composite face paradigm: role of response bias, target certainty, and feedback

Abstract: Some years ago an improved design (the “complete design”) was proposed to assess the composite face effect in terms of a congruency effect, defined as the performance difference for congruent and incongruent target to no-target relationships (Cheung et al., 2008). In a recent paper Rossion (2013) questioned whether the congruency effect was a valid hallmark of perceptual integration, because it may contain confounds with face-unspecific interference effects. Here we argue that the complete design is well-balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…2b), incorporating identical and different distractor halves and all four trial types (e.g., Cheung, Richler, Palmeri, & Gauthier, 2008;Richler, Cheung, & Gauthier, 2011a;Richler, Gauthier, Wenger, & Palmeri, 2008;Richler, Mack, Palmeri, & Gauthier, 2011). Importantly, upright face composite effects calculated using the complete and original matching designs do not correlate (Richler & Gauthier, 2014), suggesting that the variants measure different phenomena; however, the reason for the discrepancy remains contested (Meinhardt, Meinhardt-Injac, & Persike, 2014;Richler & Gauthier, 2013;Rossion, 2013).…”
Section: Original and Complete Matching Proceduresmentioning
confidence: 84%
“…2b), incorporating identical and different distractor halves and all four trial types (e.g., Cheung, Richler, Palmeri, & Gauthier, 2008;Richler, Cheung, & Gauthier, 2011a;Richler, Gauthier, Wenger, & Palmeri, 2008;Richler, Mack, Palmeri, & Gauthier, 2011). Importantly, upright face composite effects calculated using the complete and original matching designs do not correlate (Richler & Gauthier, 2014), suggesting that the variants measure different phenomena; however, the reason for the discrepancy remains contested (Meinhardt, Meinhardt-Injac, & Persike, 2014;Richler & Gauthier, 2013;Rossion, 2013).…”
Section: Original and Complete Matching Proceduresmentioning
confidence: 84%
“…Here, we extended these findings, using the composite task, which has been more widely used as a measure of holistic processing (e.g. Cheung et al, 2008; Curby et al, 2013; De Gutis et al, 2013; Gao et al, 2011; Meinhardt et al, 2014; Rossion, 2013; Zhou et al, 2012). In line with McKone (2009), we found that the magnitude of holistic processing was lower as faces were made smaller (i.e.…”
Section: Discussionmentioning
confidence: 67%
“…However, it is standard in group studies to use the interaction between congruency and alignment, as misalignment greatly reduces the congruency effect (Richler & Gauthier, 2014). The main advantage of the congruency x alignment effect over the alignment effect is robustness to manipulations that influence a particular response bias associated with alignment and congruency (as reviewed by Richler & Gauthier, 2014; see Meinhardt et al, 2014 for the same conclusion). In theory, both measures may tap into the same failures of selective attention in aligned faces, but the two effects show little relation across studies (r = .27, p=.18; Richler & Gauthier, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although we believe that the alternative variant offers a more balanced design by including a congruency factor, we suggest that researchers should beware of interpretations based on the Congruency 3 Alignment interaction. It is common in research with the alternative design to calculate sensitivity measurements to discriminate between true discriminability (d 0 ) and response bias (criterion c; e.g., Cheung, Richler, Palmeri, & Gauthier, 2008;DeGutis, Wilmer, Mercado, & Cohan, 2013;Gauthier & Bukach, 2007;Horry, Cheong, & Brewer, 2015;Meinhardt et al, 2014;Richler, Cheung, & Gauthier, 2011;Richler, Mack, Palmeri, & Gauthier, 2011). However, we did not follow this tradition in the current study.…”
Section: Alternative Versus Standard Designmentioning
confidence: 98%
“…The main difference between the two versions is the number of manipulated factors (see Figure 2), but the standard design can easily be extracted from the alternative design. For this reason, and because research on reliability and response bias seems to point to the alternative variant as the preferable design (Meinhardt, Meinhardt-Injac, & Persike, 2014;Richler, Cheung, & Gauthier, 2011), we opt for this variant in the present study. As can be seen in Figure 2, in the alternative design three factors are manipulated independently: similarity, congruency, and alignment.…”
Section: Present Studymentioning
confidence: 99%